Poly (DL-valine) electro-polymerized carbon nanotube paste sensor for determination of antihistamine drug cetirizine - Tigari Girish (Journal of Electrochemical Science and Engineering, 2020)
Poly (DL-valine) modified multiwalled carbon nanotube paste sensor (PVLMCNTPS) was prepared by electro-polymerization route. PVLMCNTPS and bare multiwalled carbon nanotube paste sensor (BMCNTPS) morphologies and sensing properties for cetirizine (CTZ) were confirmed through a field emission scanning electron microscope (FE-SEM) and electrochemical studies, respectively. In contrast to BMCNTPS, PVLMCNTPS surface composite creates an electrocatalytic impact on the oxidation of CTZ. PVLMCNTPS properties were optimized using parameters such as accumulation time, number of polymerization cycles, solution pH, and scan rate. The optimized PVLMCNTPS was applied for the determination of cetirizine in 0.1 M phosphate buffer solution (PBS) of pH 7.0, using cyclic voltammetry (CV). It is shown that PVLMCNTPS provided analytical linearity from 2.0 to 80 µM, with a detection limit of 0.11 µM for CTZ determination. PVLMCNTPS is found highly selective for CTZ in presence of some interfering organic molecules. The stable and selective PVLMCNTPS was applied for CTZ determination in pharmaceutical pills with satisfactory results.